Wojciech Ryszard Rzepka na tle poznańskiej tradycji językoznawstwa historycznego - Walczak, Bogdan (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article is an attempt to establish the position of the scholarly achievements of Wojciech Ryszard Rzepka (almost exclusively in the field of the history of the Polish language) on the background of the scholarly activity of his predecessors. The author adopted the output of his teacher and scholarly master, Władysław Kuraszkiewicz, as the most important reference point. The author has examined more closely three currents in the research activity of Wojciech Rzepka: his lexical studies, his editorial and lexicographical output. Concluding the article, the author considered Rzepka most prominent historian of the Polish language in his generation – a researcher whose scholarly achievements are marked by originality and novelty as well as a harmonious combination of the dominating empiricism and understanding for the theory and methodology of historical linguistics.